2019
DOI: 10.1002/ange.201910225
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth of CH3NH3PbBr3 Perovskite Nanocrystals via a Water–Oil Interfacial Synthesis Method

Abstract: Fundamental insights into the reaction kinetics of organic-inorganic lead halide perovskite nanocrystals (LHP NCs) are still limited due to their ultrafast formation rate. Herein, we develop aw ater-oil interfacial synthesis of MAPbBr 3 NCs (MA = CH 3 NH 3 + ), whichp rolongs the reaction time to tens of minutes.T his method makes it possible to monitor in situ the formation process of MAPbBr 3 NCs and observe successive spectral evolutions from 438 to 534 nm in asingle reaction by extending reaction time.T he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Recently, Li et al. have reported a slow crystal growth of CH 3 NH 3 PbBr 3 perovskite NC on oil–water interface . Kostopoulou et al.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Li et al. have reported a slow crystal growth of CH 3 NH 3 PbBr 3 perovskite NC on oil–water interface . Kostopoulou et al.…”
Section: Figurementioning
confidence: 99%
“…[19] However,w hen these two ligandsa re used together,t hey form the oleate anion and olylammonium cation,w hich are better cappinga gentsd ue to the strong interaction with Pb 2 + and X À ,r espectively. [21] Kostopoulou et al very recently reported as low growth of CsPbBr 3 nanowirei nt oluene and as idet os ide coalescence of the nanocrystals is proposed as the mechanism. Akin to most of the nanomaterials, the properties of perovskite NCs dependh ighly on their size and shape.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…35,36 Previous studies revealed the accelerating effect of polar solvents in ionization and an ion exchanging process during the growth of metal salts, while the nucleation rate largely depends on the diffusion of the precursors and monomers in solvents. [37][38][39][40] ODE possesses high viscosity and low polarity that are negative for the separation of the nucleation and growth of the PNCs at low temperature. We infer that the solvents with low viscosity and appropriate polarity will benefit the homogenous growth of PNCs.…”
Section: Resultsmentioning
confidence: 99%
“…As illustrated in Figure b, by dispersing various ion sources in immiscible two-phase solvents, precursors will slowly diffuse to the interface and initiate reactions. This approach has demonstrated continuous size tuning . Despite its merits, challenges persist in enhancing the stability and optical properties of the resulting NCs due to the use of polar solvents.…”
Section: Remarks and Future Outlookmentioning
confidence: 99%